Numerical investigation on condensation heat transfer performance of mixed hydrocarbon refrigerant in spirally tubes. (July 2022) - Tian, Zhongyun; Zheng, Wenke; Li, Xuanping; Zheng, Liwen; Jiang, Yiqiang
Abstract: The spiral wound heat exchanger (SWHE) has been recognized as the first choice for large-scale liquefied natural gas plants, in which the condensation characteristic in the spiral tube plays an essential role in the SWHE. In this study, a numerical model is built in accordance with the SWHE parameter and then verified. The condensation characteristics of methane/ ethane/ propane (mole fraction: 0.4/ 0.3/ 0.3) mixed hydrocarbon mediums in spiral tube are studied. And, the effects arising from mass flux, saturation pressure, and vapor quality on void fraction, heat transfer coefficient and friction pressure drop are explored. A conclusion of this study is drawn, showing that the void fraction increases by 56.14% with the increase in the vapor quality from 0.1 to 0.9; the void fraction increases by 12.67% with the mass flux increasing from 200 kg(m 2 s) −1 to 600 kg(m 2 s) −1 . Moreover, the heat transfer coefficient increases monotonously with the increase of the vapor quality when the mass flux is 200 kg(m 2 s) −1 ; at 400 and 600 kg(m 2 s) −1, the heat transfer coefficient and the friction pressure drop increase first and then tend to be smooth or decrease slightly at high vapor quality. This study provides a reference for the design, development, and application of the large-scale SWHE.